2015
DOI: 10.1111/wrr.12258
|View full text |Cite
|
Sign up to set email alerts
|

Organic light emitting diode improves diabetic cutaneous wound healing in rats

Abstract: A major complication for diabetic patients is chronic wounds due to impaired wound healing. It is well documented that visible red wavelengths can accelerate wound healing in diabetic animal models and patients. In vitro and in vivo diabetic models were used to investigate the effects of organic light emitting diode (OLED) irradiation on cellular function and cutaneous wound healing. Human dermal fibroblasts were cultured in hyperglycemic medium (glucose concentration 180 mM) and irradiated with an OLED (623 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 36 publications
(76 reference statements)
2
39
0
Order By: Relevance
“…Under severe conditions, chronic diabetic ulcers of the feet and lower extremities will develop, and many patients with diabetes eventually require amputation. Traditional treatments for diabetic wounds are timeconsuming and laborious, and the results are often unsatisfactory (3,6). In addition, several previous studies have reported new nonpharmacological therapies, such as hyperbaric oxygen therapy, photobiomodulation and low-level laser therapy (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under severe conditions, chronic diabetic ulcers of the feet and lower extremities will develop, and many patients with diabetes eventually require amputation. Traditional treatments for diabetic wounds are timeconsuming and laborious, and the results are often unsatisfactory (3,6). In addition, several previous studies have reported new nonpharmacological therapies, such as hyperbaric oxygen therapy, photobiomodulation and low-level laser therapy (34).…”
Section: Discussionmentioning
confidence: 99%
“…Wounds in patients with diabetes heal more slowly or are nonhealing. Moreover, persistent chronic skin ulcers are present in diabetic skin wounds (3). Impaired wound healing has complex underlying pathogeneses, such as a prolonged inflammatory response, inadequate angiogenesis, and decreased fibroblast mitogenesis and growth factor production (4).…”
mentioning
confidence: 99%
“…These studies have implicated decreased pro‐inflammatory cytokines (TNF α , IL1 β , IL6), mast cell degranulation, altered MMPs and redox status, decreased cell adhesion complexes as well as modulated bFGF signaling as key players in PBM modulated DM wound healing . There have been specific studies designed to assess the effects of wavelengths, dose, light sources (including OLEDs), pulsing as well as combinations with nutritional supplements such as CoQ10 that have all shown positive correlations .…”
Section: Discussionmentioning
confidence: 99%
“…These studies have implicated decreased pro-inflammatory cytokines (TNFa, IL1b, IL6), mast cell degranulation, altered MMPs and redox status, decreased cell adhesion complexes as well as modulated bFGF signaling as key players in PBM modulated DM wound healing (22)(23)(24)(25)(26)(27). There have been specific studies designed to assess the effects of wavelengths, dose, light sources (including OLEDs), pulsing as well as combinations with nutritional supplements such as CoQ10 that have all shown positive correlations (12,(28)(29)(30)(31)(32)(33)(34)(35)(36). Histological assessment (criteria outlined in Table S2) for re-epithelization and inflammation was performed in each treatment group at day 4 and 10 PBM post-treatments.…”
Section: Discussionmentioning
confidence: 99%
“…PBM with red light has been demonstrated to improve diabetic wound healing by accelerating collagen production, enhancing angiogenesis, increasing wound closure rate, and increasing growth factor expression. While OLEDs have been applied to improve diabetic cutaneous wound healing in rats, their broad emission peaks and relatively low power density remains a major factor limiting their treatment effects [12,13].…”
Section: Flexible Qleds For Treatment Of Two Specific Diseases: Diabementioning
confidence: 99%